(untitled) (Ekonomski vjesnik/Econviews - Review of Contemporary Business, Entrepreneurship and Economic Issues, 2022)
Purpose: Development opportunities of higher education institutions (HEI) arising from international activities are constantly evolving, increasing at the same time their complexity. Consequently, numerous activities have been created to connect different higher education institutions across Europe, where the biggest challenge of internationalisation today is the European Universities Initiative. In that context, it is important to measure whether the European Union initiative created better resilience to the COVID-19 pandemic. Methodology: Empirical analysis was conducted that included international students who studied at UNIST for one semester during the pandemic. The following descriptive statistics methods were used for data analysis: percentages, mean, frequency distribution, the standard deviation correlation method, as well as the independent-samples t-test and the correlation method. Results: The results show that from the perspective of international students, there is a positive relationship between perceived service quality and internationalisation during the COVID-19 pandemic period. A case study was presented on the internationalisation of the University of Split as one of the first universities that joined the European Universities Initiative. Conclusion: Internationalisation is one of the keys to success if the perceived quality of higher education can be considered as a key to student satisfaction.